New insights in glucocorticoid receptor signaling – more than just a ligand binding receptor - Scheschowitsch, Karin; Leite, Jacqueline A.; Assreuy, Jamil (Frontiers in Endocrinology, 2017)
The clinical use of classical glucocorticoids (GC) is narrowed by the many side effects it causes, as well as the resistance to GC observed in some diseases. Since the great majority of GC effects depends on the activation of a glucocorticoid receptor (GR), many research groups had focused in better understand the signaling pathways involving those receptors. Transgenic animal models and genetic modifications of the receptor brought a huge insight into GR mechanisms of action. This, in turn, opened a new window for the search of selective GR modulators, that ideally may have agonistic and antagonistic combined effects and activate one specific signaling pathway, inducing mostly transrepression or transactivation mechanisms. Another important research field concerns to post-translational modifications that affect the GR, and consequently also affect its signaling and function. In this mini-review we discuss many of those aspects of GR signaling, as well as findings like the ligand-independent activation of GR, which add another layer of complexity in GR signaling pathways. Although several recent data have been added to the GR field, much work has yet to be done, specially to find out the biological relevance of those alternative GR signaling pathways. Improving the knowledge about alternative GR signaling pathways and understanding how these pathways intercommunicate and in which situations they are relevant might help to develop new strategies to take benefit of it, as well as improve GC or other compounds efficacy causing minimal side effects.